A Comparative Study of the Effect of Paraffin Phase Change Material Mixture and Ice Bag on Temperature Control in Bricks - Fahrurrozi Fahrurrozi; Iwan, Muhammad; Irawan, Doddy; Gunarto Gunarto; Fahrezi, Dian; Govari, Muhammad Khoirul (International Journal of Industrial Innovation and Mechanical Engineering, 2025)
The goal of the article is to improve the thermal properties and energy efficiency of the walls and facades of the buildings by introducing the phase change material in the bricks. This study focuses on the thermal insulation capabilities of a paraffin-ice bag PCM mixture, aiming to enhance the thermal inertness of the bricks. The paraffin wax exhibits a high latent heat and is chemically stable, while the ice bags, with their low temperatures, serve as effective thermal regulators. They complement each other to address challenges such as the low thermal conductivity of paraffin and the leakage of low phase change transition temperature in paraffin. We made use of two types of paraffin and ice bag PCMs in a 50:50 ratio and embedded them in standard bricks. During the experiment, we coated the brick surfaces with liquid cement to enhance the hydraulic resistance of the PCM. Next, we inserted wires known as packing plugs into the bricks and filled the holes with powders. We also subjected the bricks to heating and cooling in cycles, ensuring the temperatures remained within a specified range. During the experiment, temperature sensors were utilized to capture data concerning thermal performance. The authors reached the conclusion that PCM polymer composite bricks possess a lot of promise such walls are being able to maintain their thermal performance parameters. When PCM-enhanced bricks are utilized, temperature changes were significantly restricted, staying constant during the times of peak heating and cooling. The PCM bricks also displayed efficient absorption and gradual release of energy due to the high energy transfer rates during phase change. This study suggests that PCM polymer composite bricks are cost-effective for the energy performance of buildings.